Autonomic dysfunction and cardiovascular risk in psoriatic arthritis - DURUÖZ, MEHMET TUNCAY (My University, 2022)
Psoriatic arthritis (PsA) is an inflammatory disease with a high prevalence of cardiovascular (CV) events due to traditional cardiovascular risk factors and increased systemic inflammation. In this review, our objectives were to (i) evaluate the cardiovascular events and risk factors and (ii) investigate the relationship between autonomic dysfunction and CV diseases in PsA. A systematic review of the literature was done on the Medline/PubMed, Scopus, and the Directory of Open Access Journals databases between January 2017 and July 2022. After screening and exclusions, 73 studies were included for the final review. Patients with PsA have a greater risk of CV diseases and increased traditional CV risk factors, including hypertension, diabetes mellitus, obesity, metabolic syndrome, and dyslipidemia. Although autonomic dysfunction is more common in PsA than in the general population, its relationship with increased CV diseases in these patients is still unclear. Limitations in explaining CV risk in these patient groups complicate patient assessment as cardiovascular risk factors are linked to the morbidity and mortality of PsA, and it is essential to improve an optimal screening and management strategy for CV disease. All CV risk scoring systems cannot fully assess the CV risk in these patients, so in addition to scoring systems, carotid ultrasound evaluation may be a part of the CV evaluation.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Autonomic nervous system; Cardiovascular abnormality; Dysautonomia; Psoriatic arthritis; SUBCLINICAL ATHEROSCLEROSIS; MYOCARDIAL-INFARCTION; RHEUMATOID-ARTHRITIS; GENERAL-POPULATION; COMORBIDITIES; DISEASE; PREVALENCE; HYPERLIPIDEMIA; MORTALITY; Autonomic nervous system; Cardiovascular abnormality; Dysautonomia; Psoriatic arthritis